Enhancement of pro‐degradant performance in polyethylene/starch blends as a function of distribution. Issue 1 (10th July 2012) - Yu, Long; Liu, Xingxun; Petinakis, Eustathios; Bateman, Stuart; Sangwan, Parveen; Ammala, Anne; Dean, Katherine; Wong‐Holmes, Susan; Yuan, Qiang; Siew, Chee Kiong; Samsudin, Farid; Ahamid, Zulkifli
Abstract The effect of pro‐degradant distribution in polyethylene (PE)/starch blends on ultraviolet (UV) photo‐oxidative degradation was investigated. Two kinds of pro‐degradants, Fe and Co‐based, were used in this study. The distribution of pro‐degradants in the different phases was varied by a dual step process using a side‐feed on a reactive extruder. The variation in mechanical properties and evaluation of carbonyl groups by FTIR were conducted to investigate the effect of degradation following exposure to UV photo‐oxidative degradation. It was found that the variation in mechanical properties was higher when the pro‐degradants were distributed in the PE phase. The concentration of carbonyl groups increased as a function of UV exposure, and the concentration of carbonyl groups was higher when the pro‐degradants were distributed in the PE phase. Micro‐cracking was observed on the interface between starch and PE after adding the pro‐degradants. When the pro‐degradants were distributed in high‐density polyethylene (HDPE) phase, the micro‐cracks mainly appeared in HDPE matrix, and the density of micro‐crack was higher. In general, the function of the pro‐degradants in PE/starch blends was enhanced when their distribution was varied within HDPE phase. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013